Listeria Species in Seafoods from two Major Fish Markets in Lagos, Nigeria - E. Esther, Amusan; A. Isiaku, Sanni; Kolawole, Banwo (Covenant Journal of Physical and Life Sciences, 2017)
Listeria is a bacterial genus thatis widely distributed in our environment. Its most economically important species is Listeria monocytogenes. Listeriosis is a serious infection caused by eating food contaminated with Listeria monocytogenes. The contamination of seafoods with Listeria species may occur during processing, handling and packaging due to poor quality control measures. The aim of this study was to isolate and identify Listeria spp. from seafoods sold at Liverpool and Makoko fish markets in Lagos. A total of 193 seafood samples including Blue Whiting (Micromesistus poutasou), Croaker (Pseudotolitus elongatus) and Pink Shrimp (Penaeus notialis) were screened for the presence of Listeria spp. The isolation and identification of Listeria species were carried out using the Oxoid Listeria Précis method. Forty-nine samples were positive for Listeria spp. and were identified as Listeria ivanovii,L. grayi, L. welshimeri, L. monocytogenes and L. innocua. Fresh croaker had the highest prevalence of 58.8%. The results of this study indicate the presence of Listeria spp. in seafoods in Liverpool and Makoko fish markets. It also revealed the possibility that these seafoods could contribute to food borne infections. Therefore, the improvement of seafood quality is of utmost importance.